EFFECT OF EMPLOYEE PERCEPTION OF TRANSFORMATIONAL LEADERSHIP, TOTAL QUALITY MANAGEMENT AND KNOWLEDGE SHARING TOWARDS ORGANIZATIONAL EFFECTIVENESS OF AN ELECTRONIC COMPONENTS MANUFACTURING COMPANY IN PATHUM THANI PROVINCE - Tassanaekjit, Onphimon; Akkawanitcha, Chuanchuen (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
This research article aims to study 1) the influence of transformational leadership on the effectiveness of organization, knowledge sharing and total quality management 2) the influence of training on the total quality management and 3) the influence of knowledge sharing and total quality management on the effectiveness of organization. The quantitative research method is employed and using questionnaires as instrument to collect data. The samples are 350 employees of an electronic components manufacturing company in Pathum Thani province. By using method of quota sampling design from employees in 4 divisions of company, then using convenience sampling design. Data is analyzed by using the structural equation modeling (SEM). The results showed that: 1) The results of hypotheses testing have found that transformational leadership have a positive influence on effectiveness of organization, Transformational leadership have a positive influence on knowledge sharing, Transformational leadership have a positive influence on total quality management. 2) Training have a positive influence on total quality management and 3) Knowledge sharing have no influence on effectiveness of organization. Furthermore, Total quality management have a positive influence on effectiveness of organization.